Coronoid height index: a reliable and reproducible technique for quantifying coronoid bone loss in elbow instability - Olamide Oyelade, BMBS; Mithun A. Joshi, MBBS (Hons), FRACS (Orth), FAOrthA; Joideep Phadnis, MBChB, FRCS (Tr & Orth), PhD (JSES International, 2024)
Background: Coronoid fracture size is one important factor in decision-making on surgical vs. nonsurgical management. There is currently no reliable, standardized technique to measure coronoid fracture size or bone loss. Hence, decision-making remains arbitrary, and recommendations made in the literature are unreliable. The aim of the study was to develop and assess a simple, reliable computed tomography (CT)-based technique that allows measurement of apical and anteromedial facet (AMF) coronoid height and bone loss. To achieve this, we sought to understand normal coronoid height across a large patient cohort, and whether the new technique was sensitive at detecting bone loss in patients with a fracture. Methods: 163 CT scans were manually formatted in the plane of the proximal ulna. A best fit circle was drawn in the greater sigmoid notch on the sagittal section. The coronoid coverage height (CCH) was defined as the distance (in mm) measured at 90° from the greater sigmoid notch floor to a line between the olecranon and coronoid tips (or fracture base in fractured coronoids), bisecting the center of the circle. The coronoid height index (CHI) was calculated as a % by dividing the CCH by the diameter of the circle. The measurements were performed at the coronoid apex and the center of the AMF in 108 intact coronoids to understand normative values and 55 fractured coronoids to assess the sensitivity of the technique at detecting bone loss. Measurements were independently performed by two investigators, and interobserver reliability was assessed with weighted Cohen’s kappa (ĸ) and intraclass correlation coefficient. Results: For intact coronoids, the mean CCH was 11.4 ± 1.4 mm at the apex and 11.6 ± 1.3 mm at the AMF. The mean CHI was 56.7 ± 4.9% at the apex and 41.1 ± 3.6% at the AMF. For fractured coronoids, the mean CCH and CHI were significantly lower (P < .001) at both the apical (9.7 ± 1.4 mm, 45.8% ± 6.5%) and AMF (9.8 ± 1.6 mm, 33.9% ± 6.5%) positions, confirming that the technique was capable of detecting coronoid bone loss. While the CCH (a metric measurement) was significantly higher in men than in women (P < .001), the CHI (a proportion) demonstrated no significant difference at both the apex (P = .06) and AMF (P = .91). Interobserver reliability was good to excellent across all parameters. Conclusion: CHI is a reliable CT-based technique to assess coronoid height and bone loss that is independent of patient size and can be used for clinical and research purposes.